Patterns and Drivers of Heavy and Extreme Hourly Rainfall Events over Metro Manila, Philippines - Taña, Enrico Alejandro S. (Archīum Ateneo, 2024)
This study investigates the spatio-temporal characteristics of heavy hourly rainfall (HHR; 95th–99th percentile) and extreme hourly rainfall (EHR; >99th percentile) events over Metro Manila, Philippines, and quantifies the percentage contributions of synoptic scale (Tropical Cyclones (TCs) and Low Pressure Systems (LPSs; weaker disturbances than TCs)) and local scale systems (convective and stratiform rainfall events) to the total HHR and EHR, during the southwest monsoon season from 2012 to 2019. The results show higher mean rainfall intensities for both HHR and EHR events in stations located further inland and close to mountainous areas. An evident afternoon peak is observed for both HHR and EHR events possibly caused by the diurnal heating over land. A secondary peak is also observed in the early morning hours for HHR events, which is likely caused by the convergence between the local wind circulations and the prevailing monsoon southwesterlies. Both HHR and EHR events are dominated by short–duration events (1–2 h) (HHR: 69–82%, EHR: 77–94%) across all stations, with higher percentages in stations located further inland near the mountainous regions. On the other hand, the contributions from medium–duration (3–5 h) (HHR: 15–26%, EHR: 4–23%) and long–duration events (≥ 6 h) (HHR: 3–9%, EHR: 0–6%) are smaller, with higher percentages located in northern stations. The majority of HHR events (52–60%) are found to be caused by stratiform rainfall, while the EHR events are mostly caused by convective rainfall events (38–72%). The contribution from TCs (LPSs) ranges from 37 to 46% (2–4%) for the HHR and 24–47% (0–5%) for the EHR events, respectively. These insights on the spatio-temporal variation of heavy and extreme rainfall events can be used in better understanding the characteristics of rainfall extremes in Metro Manila.